2006
DOI: 10.1126/science.1128721
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transposition as a Cause of Hybrid Sterility in Drosophila

Abstract: We describe reproductive isolation caused by a gene transposition. In certain Drosophila melanogaster-D. simulans hybrids, hybrid male sterility is caused by the lack of a single-copy gene essential for male fertility, JYAlpha. This gene is located on the fourth chromosome of D. melanogaster but on the third chromosome of D. simulans. Genomic and molecular analyses show that JYAlpha transposed to the third chromosome during the evolutionary history of the D. simulans lineage. Because of this transposition, a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
150
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(153 citation statements)
references
References 20 publications
2
150
1
Order By: Relevance
“…Indeed, QTL size (7.35% PVE) was at the detection limit despite the large size of the QTL population. This contrasts with recent studies in Drosophila, where several genes have recently been cloned that cause almost complete reproductive isolation (Tinget al 1998;Barbash et al 2003;Presgraves 2003;Masly et al 2006). Likewise, major QTL for sterility are frequently detected in flowering plants (Moyle and Graham 2005;Fishman and Willis 2006;Sweigart et al 2006).…”
Section: Mechanisms Of Reproductive Isolationcontrasting
confidence: 45%
“…Indeed, QTL size (7.35% PVE) was at the detection limit despite the large size of the QTL population. This contrasts with recent studies in Drosophila, where several genes have recently been cloned that cause almost complete reproductive isolation (Tinget al 1998;Barbash et al 2003;Presgraves 2003;Masly et al 2006). Likewise, major QTL for sterility are frequently detected in flowering plants (Moyle and Graham 2005;Fishman and Willis 2006;Sweigart et al 2006).…”
Section: Mechanisms Of Reproductive Isolationcontrasting
confidence: 45%
“…Duplication and differentiation between paralogs can alter the genetic architecture of male and female traits, and hybridization between species can potentially disrupt the transmission of sex-specific genes, leading to sex-specific hybrid inviability or sterility (see Lynch and Force 2000;Masly et al 2006). Gene duplication between chromosomes, particularly the movement of male functions from the X to the autosomes, can disproportionately affect males and might partially account for the two rules of speciation (Moyle et al 2010): ''Haldane's rule'' (Haldane 1922;Coyne and Orr 2004) and the ''large-X effect'' (Coyne and Orr 1989;True et al 1996;Tao et al 2003;Masly and Presgraves 2007;Presgraves 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Advanced crosses using sophisticated genetic trickery (i.e., X-ray irradiation or hybrid rescue mutations) to overcome F 1 isolation have shown that hybrid male sterility is highly polygenic and complex (Pontecorvo 1943;Sawumura et al 2000). Indeed, even the tiny dot chromosome causes hybrid male sterility in these species (Muller and Pontecorvo 1940;Masly et al 2006). In marked contrast, only a few QTL contribute to hybrid male sterility between D. virilis and D. americana, two species distinguished by roughly the same degree of synonymous genetic divergence as D. melanogaster and D. simulans (D. virilis-D. americana K s 0.11, MoralesHojas et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of Y-linked genes among the 12 sequenced Drosophila species found low conservation of gene content (Koerich et al 2008). If gene movement on and off the Y chromosome has occurred repeatedly in the D. virilis group, crosses between species might yield hybrids that lack a full complement of essential male fertility factors (see Masly et al 2006;Lynch and Force 2000). To investigate this possibility, I designed primers to PCR amplify an exon from each of the six genes known to be Y-linked in D. virilis (kl-2, kl-3, kl-5, ORY, PPr-Y, and PRY: see Koerich et al 2008).…”
Section: Discussionmentioning
confidence: 99%